TINJAUAN YURIDIS HAK-HAK PENYANDANG CACAT SEBAGAI PENUMPANG PESAWAT UDARA OLEH MASKAPAI PENERBANGAN DI INDONESIA DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 2009 TENTANG PENERBANGAN - Afrial Syarli; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Realization of the fulfillment, promotion and protection of the rights of persons withdisabilities as a passenger aircraft is still considered bad. Setting the rights ofpersons with disabilities in the legislation are still less cost and quality of service inthe fulfillment of rights of air passengers by some airlines in Indonesia is stilldiscrimination and do not carry out what is mandated by Act No. 1 of 2009 onAviation.Issues that will be examined in this study are: first, how is setting the rightsof persons with disabilities as a passenger aircraft in terms of legislation inIndonesia ?. Second, How legal protection rights of persons with disabilities as apassenger aircraft by airlines in Indonesia ?.This research is a normative legal research. This study examines the legalkonstistensi in the regulation and protection of the rights of persons with disabilitiesas a passenger aircraft by airlines in Indonesia are reviewed by Act No. 1 of 2000 onAviation. Source of data used is the source of the data obtained from the study ofliterature, among others, covers the official documents, books, tangible researchresults reports and so on. Data were analyzed qualitatively and in drawingconclusions menggunakn deductive method of thinking.Results from this study is the first, setting the rights of persons withdisabilities as a passenger aircraft is set in the Act flight and ministerial regulations,but the regulations have not accommodate the rights of persons with disabilities well,where people with disabilities are still getting treatment tend to be discriminatory, soto the government to immediately renew the laws and legislation related to thedisabled people. Second, the legal protection against the disabled as air passengersin Indonesia are not going well, due to the way people with disabilities, especially theairline against wrong so often discriminated against, Airlines diharakan improvesocialization rights of persons with disabilities in particular regarding theaccessibility of transport aircraft to the ranks directors and crew and improvingservice to the training program.Keywords: Right - Disabilities - Flights